RELIGIUSITY MODERATED HALAL TOURISM AS THE ANTECEDENT OF TOURIST SATISFACTION IN BANDUNG - Wulandari, Astri; Marcelino, Dandy; Baharta, Edwin; Taufiq, Riza (TRIKONOMIKA, 2023)
Halal Tourism is a segment of the tourism business that focuses on muslim visitors in terms of service and, of course, halal items that are safe for consumption by muslim tourists. The goal of this research is to look at how the factor of halal tourism may enhance visitor satisfaction and how this connection can be increased when controlled by the component of religiosity in Bandung. This study is part of a descriptive study with a causal link that employs explanatory statistics. SEM-PLS analysis was utilized to analyze the data from a sample of 400 respondents. This study adds to previous research that has shown that religiosity has a major moderating impact on halal tourism and tourist satisfaction. Tourist satisfaction would boost national revenue from the tourism industry while also assisting tourism resort managers in maintaining tourist contentment and getting new insights into recruiting muslim tourists with strong religious values.